Rhyme Awareness in Children With Normal Hearing and Children With Cochlear Implants: An Exploratory Study - Jing, Linye; Vermeire, Katrien; Mangino, Andrea; Reuterskiöld, Christina (Frontiers in Psychology, 2019)
Phonological awareness is a critical component of phonological processing that predicts children’s literacy outcomes. Phonological awareness skills enable children to think about the sound structure of words and facilitates decoding, and the analysis of words during spelling. Past research has shown that children’s vocabulary knowledge and working memory capacity are associated with their phonological awareness skills. Linguistic characteristics of words, such as phonological neighborhood density and orthography congruency have also been found to influence children’s performance in phonological awareness tasks. Literacy is a difficult area for deaf and hard of hearing children, who have poor phonological awareness skills. Although cochlear implantation (CI) has been found to improve these children’s speech and language skills, limited research has investigated phonological awareness in children with CIs. Rhyme awareness is the first level of phonological awareness to develop in children with normal hearing (NH). The current study investigates whether rhyme awareness in children with NH and CIs is influenced by individual differences in vocabulary knowledge, working memory and hearing experience. Using a rhyme oddity task, well-controlled for perceptual similarity, we also explored whether children’s performance was affected by linguistic characteristics of the items in the task (e.g., rhyme neighborhood density, orthographic congruency). Our results indicate that vocabulary knowledge, working memory and hearing experience have significant effects on children’s performance in a rhyme awareness task. Linguistic characteristics of the task items, on the other hand, were not found to be significant. Implications of the results and future directions are discussed.